Pengembangan Sistem Informasi Manajemen Pasien Berbasis Komputer untuk Meningkatkan Efisiensi di Rumah Sakit - Irmayana; Salam, Abdus; Muammar (Jurnal Manajemen Sistem Informasi (JMASIF), 2024)
The management of patient data, which still relies on manual record-keeping in archives or books, often leads to inefficiencies in hospital services. The lengthy data retrieval process, the risk of data loss, and the deterioration of records are significant issues that need immediate resolution. Therefore, the development of a computerized patient management information system presents a viable solution to enhance healthcare service efficiency in hospitals. This system enables faster and more secure recording and processing of patient data. With the use of computerized systems, data retrieval is expedited, patient waiting times are reduced, and services are optimized. Furthermore, the system simplifies the generation of reports, such as patient data, outpatient records, and medications administered, which would otherwise be time-consuming if handled manually. Data security is also improved with the inclusion of user verification features, ensuring that only authorized personnel can access sensitive information. While the risk of data corruption still exists, it can be mitigated through regular backup procedures. The development of this system is expected to be more widely implemented across various healthcare facilities, extending beyond hospitals to include clinics and health centers.